Mudança no uso e cobertura da terra na bacia hidrográfica do rio Araguaia e seus reflexos nos recursos hídricos, o trecho médio do rio Araguaia em Goiás - Maximiliano Bayer; Pâmela Camila Assis; Tainá Medeiros Suizu; Matheus Cardoso Gomes (Confins)
The Araguaia River basin is currently considered a prime area for economic development for the country, due to national and international demands for the production of commodities. Representing the largest fluvial system developed entirely in Brazilian territory, the Araguaia River drains part of the states of Goiás, Mato Grosso, Tocantins and Pará. Covering an area greater than 300,000 km2, the basin extends over wide areas of Cerrado Biome that have characteristics socio-environmental characteristics (climates, lithology, soil, relief, forms of use and occupation) very different. In the last four decades, large extensions of the basin have been object of an intense transformation process associated with the advance of the agricultural frontier and changes in the form of occupation, whose consequences on the natural resources of the basin, especially water resources, are beginning to be a reason of concern for the society. For the area of the Araguaia river basin in Goiás, the analysis of land use and occupation processes showed a decrease of 33,8% for forest formation, 48,9% for savanna formation and an increase of 51,50% of the areas pasture and 510,6% of the annual and perennial crop areas. Our researches also finds that, while the percentage of areas in the basin converted for different types of use such as agriculture and cultivated pastures increases, the production, loading and transportation of sediments increased throughout the drainage basin of the middle Araguaia in Goiás generating a rapid response of the fluvial system in the form of intense morphological changes originated by the accumulation of sediments in the main channel and in the associated environments. Probable effects associated to climatic change, such as the sharp decline in maximum flow values in recent years, have not yet been assessed principal et dans les environs. Les effets probables associés aux changements climatiques comme la forte diminution des valeurs de débit maximales au cours de ces dernières années n’ont pas encore été évalués.